Effect of replacing maize and starch with Shoti meal (Curcuma zedoaria) in broiler - Datta, S; Rahman, S; Islam, O; Hassan, M; Hossain, M; Islam, SMA; Rahman, MH (Bangladesh Journal of Animal Science, 2018)
The effects of raw and autoclaved Shoti (Curcuma zedoaria) meal on the growth and N utilization of growing broilers were determined. Shoti from Bangladesh Agricultural University campus was collected and sorted on the basis of white color of the rhizome. Then they were chopped into pieces, sun dried and pulverized in a flour mill. Aliquot samples were autoclaved at 1200C under 15 lb of pressure per square inch for 30 min. Autoclaved samples were stored in tightly lid contained for future use. 3 One hundred -day-old Cobb 500 broiler chicks were reared on the floor and a total of 24 growing broilers, 4 birds in each group were weighed on d 15 Two broilers were placed in each cage. There were a total of four experimental and two control (positive and negative Non-protein control) diets. Diets were fed ad libitum from day 15 to 33days. Body weight, feed intake, feed refusal and fecal weights were recorded every day. Cumulative feed efficiency per bird was calculated as the ratio of weight gained to feed consumed. Dry matter of excreta was determined from the last 10 d of feeding trial by drying aliquots of every day’s droppings by drying for 6 h at 1050C. On d 19, birds were bled to death. Immediately after slaughter, the carcasses were examined systematically. The chemical composition of Shoti meal showed that it is low in protein, fat and trace minerals and therefore mainly a source of energy. The bulk of the tuber (75 percent) consists of carbohydrates, made up of 10.6% fiber, and 64.9% nitrogen free extracts (NFE). A peculiarity of Curcuma rhizome meal contains high level of ash (9.9%) on DM basis. The results showed that at day 33, the weight of the broiler chicken fed shoti 100g, 200g, 300 g and 200g (autoclaved shoti meal)/ Kg diet was significantly different from the weight of the chicken fed on a maize-soybean diet. The birds given shoti meal consumed less feed than those provided with a maize diet. Feed efficiency or weight gain to feed ration over 19-d period was the poorest when fed 300 g Shoti/ Kg diet. Intake picked up when the shoti meal was incorporated after having been autoclaved and there was slight improvement in body weight gain as compared to that of other Shoti fed group. However, feed efficiency and body weight gain as % of initial weight remained significantly lower than the maize-soybean control. The inclusion of Shoti meal generally had an adverse effect on the apparent dry matter digestibility compared with the control diets. The group fed autoclaved shoti meal had a similar effect and the true N digestibility was the lowest when compared to those of control fed on maize-soybean meal. Thus, physical treatment like using autoclave, caused further reduction of digestibility of its N. Lipid digestibility was reduced by ingestion of shoti meal. Since the diets were isocaloric, after correction for the apparent endogenous lipid losses, which were obtained from the results of non-protein control feeding, the net faecal losses was around 66.2% of the ingested lipid against control diet fed birds. Bang. J. Anim. Sci. 2018. 47 (1): 40-46